Launch and deployment of distributed small satellite systems. (September 2015) - Crisp, N.H.; Smith, K.; Hollingsworth, P.
Abstract: The rise in launch and use of small satellites in the past decade, a result of improved functionality through technology miniaturisation and alternative design philosophies, has spawned interest in the development of distributed systems or constellations of small satellites. However, whilst a variety of missions based on constellations of small satellites have been proposed, issues relating to the launch and deployment of these distributed systems mean that few have actually been realised. A number of strategies have been proposed which enable multiple small satellites comprising a constellation to be launched together and efficiently separated on-orbit, thus reducing the total cost of launch. In this paper, two such strategies which have the potential to significantly increase the viability of small satellite constellations in Earth orbit are investigated. Deployment using natural Earth perturbations to indirectly achieve plane separations is analysed using a developed method and compared to deployment utilising the Earth–Moon Lagrange point L1 as a staging area prior to return to LEO. The analysis of three example missions indicates that these two strategies can facilitate the successful establishment of small satellite constellations in Earth orbit whilst also reducing propulsive requirements, system complexity, and/or cost. The study also found that the method of nodal precession is sensitive to the effects of orbital decay due to drag and can result in long deployment times, and the use of Lunar L1 is more suitable for constellation configurations where several satellites are present in each orbital plane. Abstract : Highlights: Comparison of two deployment methods for small satellite constellations in LEO. Development of a method of constellation deployment by indirect plane separation. Significant Δ ν savings can be realised using method of indirect plane separation. Staged return from Earth–Moon L1 enables fast and reduced Δ ν plane separation.